Fenomena Orang Tua Dalam Mengikutsertakan Anak Usia Tk (Usia 4 – 6 Tahun) Belajar Ekstra Calistung - Umi Masturoh (Universitas Islam Lamongan, 2018)
The principle of early childhood learning is playing while learning and learning while playing. Considering the importance of learning in early childhood that the main focus is to develop and develop all aspects of child development, sometimes parents still do not understand well the stages that are right for children, so it is certain that parents will force everything according to their wishes. This encourages parents to take shortcuts which they consider to be good especially for the good of their children in the future, so it is not surprising that parents include their children to participate in additional activities outside the formal activities that have become their usual routine, these additional activities are more popular with the term learning extra, which in turn is more focused on reading, writing and arithmetic or in short calistung. This study raises the phenomenon of the parents in involving their children in extra calistung learning activities, where the actions taken by these parents are a phenomenon of actions that have specific motives and causes. This research uses a phenomenological qualitative approach. The subjects of this study were children and parents from 2 different institutions, namely institutions in Gresik Selatan District, precisely in Kedamean District and Menganti District, which researchers deliberately took to express and understand the meaning behind the phenomenon of the actions taken by these parents. The instrument in this study is the researcher himself as a direct observer who is also a data collector. The focus of this study is to (1) describe the reasons parents include their children who are sitting in the kindergarten group precisely (ages 4-6 years) in extra calistung learning activities, (2) find out the meaning of extra calistung learning for children Kindergarten (4-6 years) according to the parents' version, and (3) intent that can be discussed on the phenomenon of parents involving kindergarten-aged children (4-6 years) in extra calistung learning activities